2002
DOI: 10.1038/sj.onc.1205753
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation by the oestrogen receptor α is modulated through inhibition of cyclin-dependent kinases

Abstract: We have investigated the interaction between the expression of p21 WAF1/CIP1/SDI1 , a stoichiometric inhibitor of Cdk, and the transcriptional activity of the oestrogen receptor a (ERa). Transient transfection experiments demonstrated that the expression of p21 WAF1/CIP1/SDI1 amplified the transcriptional activation by ERa. A dominant negative mutant of Cdk2 also enhanced the ERa transcriptional activity, indicating that the underlying mechanism relies on the inhibition of Cdk2 activity and cell cycle arrest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 69 publications
3
28
0
Order By: Relevance
“…Deletion constructs, CD1-567 or CD1-69 (Sabbah et al, 1999;Redeuilh et al, 2002) (Figure 3a) were used to map the region of CD1 promoter required for Brn-3b transactivation. TK-renilla reporter (included in all transfections) provided an internal control for variability in transfection efficiencies.…”
Section: Transactivation Of Cd1 Promoter By Brn-3bmentioning
confidence: 99%
“…Deletion constructs, CD1-567 or CD1-69 (Sabbah et al, 1999;Redeuilh et al, 2002) (Figure 3a) were used to map the region of CD1 promoter required for Brn-3b transactivation. TK-renilla reporter (included in all transfections) provided an internal control for variability in transfection efficiencies.…”
Section: Transactivation Of Cd1 Promoter By Brn-3bmentioning
confidence: 99%
“…Recently, we demonstrated that p21 WAF1/CIP1 selectively controls the transcriptional activity of ERa in MCF-7 cells treated by oestrogens (Redeuilh et al 2002, Fritah et al 2005. The results of chromatin immunoprecipitation assays showed that endogenous CBP and p21 WAF1/CIP1 are recruited concomitantly to ERa on the hWISP-2/CCN5 gene promoter in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Transient transfection experiments have shown that the expression of p21 WAF1/CIP1 amplified transcriptional activation by ER in a CREB-binding protein-dependent manner (Redeuilh et al 2002).…”
Section: Discussionmentioning
confidence: 99%